PERSEPSI MAHASISWA AKUNTANSI, PRAKTISI NON SYARIAH, DAN PRAKTISI SYARIAH TERHADAP PRAKTISI SYARIAH - Irdianti, Devi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2014)
The purpose of this study are as follows: (1) To determine differences in perception between accounting students andpractitioners of shariah about shariah practitioners. (2) To determine differences in the perception of non-syariahpractitioners and practitioners of shariah about shariah practitioners. (3) To determine differences in perceptionbetween accounting students and practitioners of non- shariah practitioners about shariah practitioners . Sampling method used in this study is purposive sample selection. The sample in this study was 60 accountingstudents who have studied syariah accounting the in Islamic University